“Urate and NOX5 Control Blood Digestion in the Hematophagous Insect Rhodnius prolixus” - Gandara, Ana Caroline P.; Dias, Felipe A.; de Lemos, Paula C.; Stiebler, Renata; Bombaça, Ana Cristina S.; Menna-Barreto, Rubem; Oliveira, Pedro L. (Frontiers in Physiology, 2021)
Low levels of reactive oxygen species (ROS) are now recognized as essential players in cell signaling. Here, we studied the role of two conserved enzymes involved in redox regulation that play a critical role in the control of ROS in the digestive physiology of a blood-sucking insect, the kissing bug Rhodnius prolixus. RNAi-mediated silencing of RpNOX5 and RpXDH induced early mortality in adult females after a blood meal. Recently, a role for RpNOX5 in gut motility was reported, and here, we show that midgut peristalsis is also under the control of RpXDH. Together with impaired peristalsis, silencing either genes induced decreases in egg number, hemoglobin digestion rate and hemolymph urate titers. Ultrastructurally, the silencing of RpNOX5 or RpXDH affected midgut cell, changing the cells of blood-fed insects to a phenotype resembling that the cells of unfed insects, suggesting that these genes work together in the control of blood digestion. Injection of either allopurinol (an XDH inhibitor) or uricase recapitulated the gene silencing effects, suggesting that urate itself is involved in the control of blood digestion. The silencing of each of these genes influenced the expression of the other gene in a complex way both in the unfed state and after a blood meal, revealing signaling crosstalk between the genes that influences redox metabolism and nitrogen excretion and plays a central role in the control of digestive physiology.